PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) BERBASIS KONSTRUKTIVISME PADA POKOK BAHASAN LARUTAN ASAM BASA - Sri Puji Rohmiatin; Erviyenni Erviyenni; Sri Haryati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : The purpose of this research has been to produce LKPD based on construktivisme on the subject of acid-base solution valid based on feasibility of content, language, presentation and graphic. The research was conducted in the Faculty of Education and Teachers Training University of Riau on March-June, 2019. The type of this research was Research and Development (R&D) with the 4-D development model which covers Define, Design, Develop, and Disseminate. Because time and cost limitation, this research was only done until the development step and was followed by the limited trial. The object of this research was constructivism-based student activity sheet. The data analysis technique was descriptive statistical analysis by calculating the percentage of validation’s score. The student’s activity sheet validation of eligibility result by 3 lecturers as the experts was 94.65% which categorize as valid and has already fulfilled the eligibility of contents, language, presentation, and the graphic. The student’s activity sheet validation of eligibility result by teachers as the users was 85,71% with valid categorize, It can be concluded that the student’s activity sheet that already developed can be used in the teaching and learning process. Based on the limited trial that already done to 12 students, the respond showed 94,45% which in the positive criterion.Key Words: Development, LKPD, Constructivism, Acid-Base Solution